Serbia : Human Capital and Jobs - World Bank (World Bank, Washington, DC, 2020)
Several key policy documents guiding the broader education sector to align with European Union (EU) standards have recently been adopted in Serbia. However, a range of challenges have made it difficult for new policies and the systems they propose to be implemented. The gap between policy intentions and practice is not unique to Serbia, and old problems sometimes require new solutions. This note therefore proposes a new way of approaching higher education system reform by changing practice to inform policy, rather than the more common top-down approach.